Mothers' experiences of wellbeing and coping while living with rheumatoid arthritis: a qualitative study - Chloe Parton; Jane M. Ussher; Janette Perz (BMC, 2022)
Abstract Background Rheumatoid arthritis (RA) can result in difficulties for mothers when undertaking daily care activities and increased psychological distress. However, few studies have examined how women with RA subjectively experience coping and wellbeing as part of their motherhood. Methods Twenty mothers with a diagnosis of RA and a dependent child (18 years or younger) who were living in Australia took part in a semi-structured interview between June and November 2017. Purposive sampling was undertaken to include participants across degree of current RA severity, number and age of children, and having received a diagnosis before or after a first child to take account of variability across these experiences. A qualitative thematic analysis was conducted on the interview transcripts. Results The following themes were identified: 'Burden and complexity in the mothering role', 'Losing control: Women's experiences of distress', and 'Adjusting and letting go: Women's experiences of wellbeing'. Experiences of distress, including feelings of failure, were associated with accounts of a loss of control over mothering practices among women, regardless of child age. In contrast, accounts of adjusting mothering practices and relinquishing control were associated with reports of enhanced wellbeing. In addition, some mothers reported greater ease due to increased independence of older children. The absence of social support exacerbated burden and distress in the women's accounts, while the availability of support alleviated burden and was associated with reports of wellbeing. Conclusion Health professionals and services can provide support to mothers with RA by addressing feelings of failure, acknowledging strategies of adjustment and letting go, and encouraging access to social support.